Economic Situation of the Ottoman Period in Diyarbakir - Yılmazçelik, İbrahim (Celal ÖNEY, 2018)
Diyarbakir ever since ancient times, the Black Sea is located in Mesopotamia and the Persian Gulf to the Mediterranean Sea connecting important points. For this reason, it has been an important center in each period. At the same time the commercial importance of the East-West and North-South Anatolia junction on the caravan routes to Iran and Azerbaijan also maintained during the Ottoman Empire and has been extremely important commercial center.In this study, Ottoman administration in 1515 from the date of important commercial centers in Diyarbakir province is considered the economic situation. In particular, focus was given to the 18th and 19th centuries.The subject is dealt with under four main headings. In the first chapter markets, khans and bazaars have been described. Second, Diyarbakir has been described and presented in the commercial availability of goods and trade group of Diyarbakir production levels accordingly. The third chapter examines the sources of income in Diyarbakir. Important sources of income include farming, comes the issue of land and mukataa. These issues are explored in detail. made emphasis on customs revenues and Diyarbakir Customs is also discussed. The production and trade issues are discussed in the fourth section.

Diyarbakır hep eski çağlardan beri, Basra Körfezi ile Mezopotamya’yı Karadeniz ile Akdeniz’e bağlayan önemli noktada yer almaktadır. Bu sebeple her dönemde önemli bir merkez olmuştur. Aynı zamandaİran ve Azerbaycan’a kervan yolları üzerinde Doğu-Batı ve Kuzey-Güney Anadolu kavşağındaki ticari önemini Osmanlı İmparatorluğu döneminde de korumuş ve son derece önemli ticari bir merkez olmuştur.Bu çalışmada, Osmanlı İmparatorluğu idaresinde 1515 tarihinden itibaren önemli bir ticari merkezolan Diyarbakır Vilayetinin, ekonomik durumu ele alınmıştır. Özelikle 18. ve 19. Yüzyıllara ağırlık verilmiştir.Konu üç ana başlık altında ile ele alınmıştır. Birinci bölümde pazarlar, hanlar ve çarşılar tarif edilmiştir.İkincisinde, Diyarbakır’da, mal ve ticaret gruplarının ticari durum tarif edilmiştir ve buna göre Diyarbakır’ınüretim seviyesi sunulmuştur. Üçüncü bölümde Diyarbakır’ın gelir kaynakları incelenmiştir. Önemli gelir kaynakları arasında Tarım, arazi ve mukataa konuları gelmektedir. Bu konular ayrıntılı olarak incelenmiştir.Gümrük gelirlerine de vurgu yapılmış ve Diyarbakır Gümrüğü de ele alınmıştır. Dördüncü bölümde ise üretimve ticaret konusu ele alınmıştır.
Osmanlı Döneminde Diyarbakır Vilayeti’nin Ekonomik Durumu